Editorial for the Special Issue “Mathematical Developments in Modeling Current Financial Phenomena” - Camelia Oprean-Stan; Voichița Adriana Radu (Mathematics)
Systemic challenges, behavioral complexities, and rapid technological integration have all contributed to the astonishing pace of change in the global financial landscape [...]